Connecting the dots between battlefield tourism and creative tourism: the case of the Peninsular War in Portugal - Noivo, M. A.; Dias, Á.; Jiménez-Caballero, J. L. (Journal of Heritage Tourism, 2022)
This exploratory research provides insights into the intersection between battlefield tourism and creative tourism in Portugal. Battlefield tourism focused on the Peninsular Wars has drawn the attention of the local stakeholders, although being an under-researched academic theme. Furthermore, limited research has been found about the dynamics within battlefield tourism and creative tourism despite its impact on communities, touristic experiences and themed events. As such, this study aims (i) to identify factors that contribute to enhancing heritage through Battlefield Tourism and if in heritage-themed tourism events like re-enactment and historical recreations play an important role in the touristic activation of a community; (ii) to clarify the role of stakeholders, creative tourism experiences and tourist perceptions as part of battlefield tourism development. By leading in-depth interviews with stakeholders (tourism agents, guides and tour operators), findings reveal that stakeholders value Re-enactment and Living History as part of the creative experience, promoting interactive, diverse, and more enriching contact with local culture. Creative Tourism appeared as a key driver in the success of tourism in these destinations, enhancing local communities’ participation, network cooperation, sustained development, local identity, and ethnographic memory. Finally, theoretical contributions and new lines of investigation are discussed.